DESAIN BATIK, BRAND IMAGE, DAN BUDAYA KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA ETHNIC BATIK DAN CRAFT KLATEN JAWA TENGAH - Yesi Ade Pratiwi; Ida Aryati; Burhanudin Ahmad Yani (ITB AAS INDONESIA Surakarta, 2020)
The purpose analyze the effect of either simultaneously and partal batik designs, brand image, and consumer culture on purchasing decisions on Ethnic batik and Craft in Klaten, Central Java. The type of descriptive is quantitative. Population is Ethnic batik consumers and Craft Klaten who make transactions. The sample is 100 consumers. Data obtained from questionnaires with accidental sampling sampling techniques. F test results prove that batik design, brand image, and consumer culture simultaneously influence purchasing decisions on Ethnic Batik and Craft Klaten in Central Java, where the value of Fcount = 27,027> Ftable = 2.70 with a significance value of 0.000 1.985 significant value 0.008 1.985 and significant 0.008 1.985 and significant 0.006